The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.schres.2017.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Structural anomalies of the peripheral olfactory system in psychosis high-risk subjects

Abstract: Psychosis-risk youths exhibit an array of sexually dimorphic and laterally asymmetric anomalies of the peripheral olfactory system. These are consistent with a developmental disruption primarily affecting male fetuses. These structural biomarkers may enhance the identification of at-risk subjects with poor prognosis, before their clinical trajectory is apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 65 publications
1
18
0
1
Order By: Relevance
“…While initial high‐risk studies suggested that olfactory impairments might be specific predictors of actual conversion to schizophrenia, more recent data suggest that this is an index of poor functional outcome which may include overt psychosis, but which is an ominous marker of neurodevelopmental aberration independent of future diagnosis. Thus, our results are consistent with and reinforce the hypothesis that embryonic insults early in fetal development, which can give rise to both structural and behavioral olfactory anomalies, result in a heightened, but not inevitable, risk for both psychosis and overall functional impairment. Actual psychosis, if it emerges, may span the schizophrenia‐bipolar spectrum, with more widespread olfactory dysfunction observed in schizophrenia …”
Section: Discussionsupporting
confidence: 90%
“…While initial high‐risk studies suggested that olfactory impairments might be specific predictors of actual conversion to schizophrenia, more recent data suggest that this is an index of poor functional outcome which may include overt psychosis, but which is an ominous marker of neurodevelopmental aberration independent of future diagnosis. Thus, our results are consistent with and reinforce the hypothesis that embryonic insults early in fetal development, which can give rise to both structural and behavioral olfactory anomalies, result in a heightened, but not inevitable, risk for both psychosis and overall functional impairment. Actual psychosis, if it emerges, may span the schizophrenia‐bipolar spectrum, with more widespread olfactory dysfunction observed in schizophrenia …”
Section: Discussionsupporting
confidence: 90%
“…However, this warrants further exploration in subjects who convert. Abnormalities in the olfactory system have been reported in CHR subjects ( 138 ). Bilateral reductions in olfactory bulb volume in males, as well as reduced left olfactory grey matter volume, were observed in subjects at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…This study had several limitations. First, there was no assessment of other olfactory structures like the olfactory bulb, which also reflects olfactory system underdevelopment in psychosis [31], but could not be reliably measured on T1-weighted images. Second, while the olfactory deficit in our ARMS and schizophrenia subjects may imply orbitofrontal dysfunction [2, 21], neurocognitive (e.g., decision-making [32]) and neuroimaging data on OFC function were not available.…”
Section: Discussionmentioning
confidence: 99%